2004
DOI: 10.1128/jcm.42.5.2317-2320.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of the fsr Locus and of Gelatinase Production among Different Subsets of Enterococcus faecalis Isolates

Abstract: We examined 215 Enterococcus faecalis isolates and found that neither the two-component regulatory locus fsr (E. faecalis regulator) nor gelatinase production was more common in disease-associated isolates than in isolates colonizing healthy individuals (ca. 60 to 65%). The majority of gelatinase-negative isolates, including 14 endocarditis isolates (of 80 isolates tested), contained the previously described 23.9-kb deletion and lacked fsrA and fsrB. While these findings indicate that neither fsr nor gelatinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 28 publications
3
52
1
Order By: Relevance
“…When combined with the translocation results obtained from the previous study (31) and our subsequent determination of their gelatinase activity (17), the capability of translocation of the two groups (GelE ϩ versus GelE Ϫ ) is significantly different, with translocation occurring in a total of 167 out of 185 transwells at 6 h for GelE ϩ strains compared to a total of 7 out of 128 transwells for GelE Ϫ strains (P Ͻ 0.001 by Fisher's exact test). On the other hand, the level of translocation by gelatinase-positive human isolates varied considerably, which cannot be completely explained by the level of gelatinase activity, suggesting that although gelatinase is critical for E. faecalis translocation, other factor(s) are also important in this process.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…When combined with the translocation results obtained from the previous study (31) and our subsequent determination of their gelatinase activity (17), the capability of translocation of the two groups (GelE ϩ versus GelE Ϫ ) is significantly different, with translocation occurring in a total of 167 out of 185 transwells at 6 h for GelE ϩ strains compared to a total of 7 out of 128 transwells for GelE Ϫ strains (P Ͻ 0.001 by Fisher's exact test). On the other hand, the level of translocation by gelatinase-positive human isolates varied considerably, which cannot be completely explained by the level of gelatinase activity, suggesting that although gelatinase is critical for E. faecalis translocation, other factor(s) are also important in this process.…”
Section: Discussionmentioning
confidence: 98%
“…A 23.9-kb deletion involving fsrA and fsrB was first described by Nakayama et al in E. faecalis urine isolates obtained from a Japanese hospital (13), and this region was later found by our group, using colony hybridization and PCR, to be absent in 60 E. faecalis isolates (including TX1332 and JH2-2) from different clinical and geographical sources, which account for ca. 28% of the E. faecalis isolates tested by us (17). Neither TX1322 nor JH2-2 showed detectable gelatinase activity or translocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical enterococcal strains, gelatinase activity is generally associated with virulence factors (Pillai et al, 2002;Roberts et al, 2004). Because of no detection of gelatinase activity or presence of fsr and gelE genes in the tested clinical E. faecium isolates, no significant correlation was found between gelatinase production and fsr, gelE genes and biofilm formation.…”
Section: Occurrence Of Esp Fsr and Gelementioning
confidence: 83%
“…One study showed that 100% (12 out of 12) of the E. faecalis endocarditis isolates tested had fsr compared to only 53% (10 out of 19) of the fecal isolates tested (21). In contrast, two subsequent studies did not show an increased prevalence of fsr in E. faecalis endocarditis and bloodstream isolates (11,23). In a rat endocarditis model, an E. faecalis mutant that did not produce gelatinase or serine protease had an endocarditis induction rate that was significantly reduced compared to that of wild-type E. faecalis (28).…”
mentioning
confidence: 96%